God Humanization in Oka Rusmini's "Putu Menolong Tuhan" - Benedictus Bherman Dwijatmoko (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
Oka Rusmini's short-story "Putu Menolong Tuhan" is an ironical story of a child who feels the need to kill her grandmother to help God. A Critical Discourse Analysis of the story reveals the ideology of the humanization of God. In response to the mean treatment of her grandmother to her mother, Putu murders her grandmother. She murders her grandmother because God loves a good person and hates a bad person and her grandmother is a bad person. The murder can be understood as an act of humanizing God. The understanding of God humanization gains its significance as the attack to government officials and the bombings of public places in several cities in Indonesia used religion as the reason. The murder of the grandmother and the violence have the same pattern: the presence of a problematic religious doctrine, a deviant character, and irrational moral self-superiority.